EDUKASI PENGOLAHAN PUDING DAUN KELOR SEBAGAI UPAYA PENCEGAHAN STUNTING DI DESA PENGENJEK LOMBOK TENGAH - Hasina, Raisya; Aini, Siti Rahmatul; Saputra, Yoga Dwi; Andanalusia, Mahacita; Nugrahani, Baiq Dwiyan; Lestari, Dian Fathita Dwi; Arzaqi, Yazid Maula; Nurhidayah, Afifah (Universitas Mataram, 2024)
The national government is still addressing stunting as a major problem, including NTB, so it is expected that the stunting problem will be resolved by 2023. But until now, problems related to stunting still occur in Indonesia, especially in NTB. Based on data obtained from the Bonjeruk Health Center, Central Lombok Regency, Pengenjek Village is a village in NTB with the highest stunting rate at 17%. Providing nutritious food is an effort to overcome the problem of stunting in children under five years of age. This activity aims to provide knowledge and skills about moringa pudding processing as an effort to prevent stunting. This activity was carried out in the Pengenjek Village office hall with lecture, discussion and demonstration methods of moringa leaf pudding processing. The targets of this activity are 50 mothers who have children under five years of age and 10 posyandu cadres. There are several stages in this activity, including: preparation stage, delivery of material on stunting and demonstration of making moringa leaf pudding. The preparation stage was carried out by discussing with the Head of Pengenjek Village regarding the place and schedule of implementation. The implementation of the activity was carried out in three sessions. In the first session, namely the delivery of material and discussion. The second session was a demonstration of moringa pudding processing. The third session was a question and answer session and the distribution of door prizes for participants who could answer questions and demonstrate moringa pudding processing.